Unmissing : a thriller - Kent, Minka (Thomas & Mercer, 2022)
"Merritt Coletto and her husband, Luca, have the life they dreamed of: a coastal home, a promising future, and a growing family. That dream ends with a late-night knock on the door. Weak, broken, and emaciated, it's Luca's first wife, Lydia. Missing for ten years, presumed dead, and very much alive, she has quite a story. Her kidnapping. A torturous confinement that should've ended with her dead. And finally, escape. Racked with guilt over the beautiful life they've built, Merritt and Luca agree to help get Lydia back on her feet, it's the least they can do. But the more enmeshed Lydia becomes in Merritt's family, the more questions Merritt has. What is it about Lydia that's especially unnerving? Why hasn't she gone to the police with her harrowing tale? What does she really want of them? The answers, when they come, are terrifying. Because Lydia isn't the only one with secrets"--